Bread baking as a moving boundary problem. Part 2: Model validation and numerical simulation - Purlis, Emmanuel; Salvadori, Viviana O. (Journal of food engineering, 2009)
A simultaneous heat and mass transfer model proposed to describe the bread baking process is validated. The mathematical model is based on a moving boundary problem formulation with equivalent thermophysical properties and includes the moving evaporation front, the evaporation–condensation mechanism and the development of the crust observed during bread baking. The problem is solved over an irregular three-dimensional geometry using the finite element method. Variation in temperature and water content of bread during baking is predicted with high accuracy by the model. Parameter estimation procedure and sensitivity analysis are performed for some thermophysical properties. The proposed formulation and analysis can be applied for other bakery products as well as for similar food engineering applications.